The Appearance of Broiler That Given Golden Apple Snail Meat (Pomacea canaliculata) Flour as Replacement of Fish Flour - Gordianus Jawa; Ni Ketut Etty Suwitari; I Gusti Agus Maha Putra Sanjaya (Warmadewa University Press, 2020)
The purpose of this study was to determine the effect of giving golden snail meat flour in broiler rations aged 2-5 weeks to the appearance of broiler chickens and to find out what level of golden snail meat flour can give the results of body weight gain, final body weight, feed consumption, and conversion best ration. This study used a Completely Randomized Design with 5 treatments and 3 replications for each treatment. The five treatments were rations without the content of golden snail meat flour as control and rations containing golden snail meat flour 5%, 10%, 15%, and 20%. The parameters observed were bodyweight gain, final body weight, feed consumption, and FCR (Feed Conversion Ratio). The data obtained were analyzed by analysis of variance. If between treatments showed a real difference, then proceed with Duncan's test. The results of the study of the addition of golden snail meat flour (Pomacea canaliculata) in broiler chicken rations had a very significant effect (P<0.01) on the research variables' weight gain, final body weight, and lower FCR. Whereas the consumption of rations had a significant effect (P<0.05). In treatment R2 (10%) gave better results than other treatments (R0, R1, R3, and R4). This means that the treatment of giving golden snail meat flour in the ration apparently can increase the weight gain of broiler chickens. This is because the golden snail contains quite high protein. From the results of this study, it can be concluded that the administration of golden snail meat flour (Pomacea canaliculata) in broiler rations has a very significant effect on increasing weight gain, final weight, and decreasing FCR and significantly influencing ration consumption.